Mechanisms of action for stigma reduction among primary care providers following social contact with service users and aspirational figures in Nepal: an explanatory qualitative design - Bonnie N. Kaiser; Dristy Gurung; Sauharda Rai; Anvita Bhardwaj; Manoj Dhakal; Cori L. Cafaro; Kathleen J. Sikkema; Crick Lund; Vikram Patel; Mark J. D. Jordans; Nagendra P. Luitel; Brandon A. Kohrt (International Journal of Mental Health Systems, 2022)
Abstract Background There are increasing initiatives to reduce mental illness stigma among primary care providers (PCPs) being trained in mental health services. However, there is a gap in understanding how stigma reduction initiatives for PCPs produce changes in attitudes and clinical practices. We conducted a pilot randomized controlled trial of a stigma reduction intervention in Nepal: REducing Stigma among HealthcAre Providers (RESHAPE). In a previous analysis of this pilot, we described differences in stigmatizing attitudes and clinical behaviors between PCPs receiving a standard mental health training (mental health Gap Action Program, mhGAP) vs. those receiving an mhGAP plus RESHAPE training. The goal of this analysis is to use qualitative interview data to explain the quantitative differences in stigma outcomes identified between the trial arms. Methods PCPs were randomized to either standard mental health training using mhGAP led by mental health specialists or the experimental condition (RESHAPE) in which service users living with mental illness shared photographic recovery narratives and participated in facilitated social contact. Qualitative interviews were conducted with PCPs five months post-training (n = 8, standard mhGAP training; n = 20, RESHAPE). Stigmatizing attitudes and clinical practices before and after training were qualitatively explored to identify mechanisms of change. Results PCPs in both training arms described changes in knowledge, skills, and confidence in providing mental healthcare. PCPs in both arms described a positive feedback loop, in which discussing mental health with patients encouraged more patients to seek treatment and open up about their illness, which demonstrated for PCPs that mental illness can be treated and boosted their clinical confidence. Importantly, PCPs in the RESHAPE arm were more likely to describe a willingness to treat mental health patients and attributed this in part to social contact with service users during the training. Conclusions Our qualitative research identified testable mechanisms of action for stigma reduction and improving clinical behavior: specifically, recovery stories from service users and social engagement led to greater willingness to engage with patients about mental illness, triggering a feedback loop of more positive experiences with patients who benefit from mental healthcare, which further reinforces willingness to deliver mental healthcare. Trial registration ClinicalTrials.gov identifier, NCT02793271